What Makes a School a Learning Organisation? - Kools, Marco (OECD Publishing, 2016)
What are the characteristics of a school as learning organisation? This paper should be seen as an attempt to work towards a common understanding of the school as learning organisation concept that is both solidly founded in the literature and is recognisable to all parties involved, i.e. educators, policy makers, parents and others alike. The paper provides an in-depth analysis of the learning organisation literature in general, and within a school context. It identifies and operationalises the characteristics of the school as learning organisation in an integrated model that consists of seven overarching 'action-oriented' dimensions: 1) developing and sharing a vision centred on the learning of all students; 2) creating and supporting continuous learning opportunities for all staff; 3) promoting team learning and collaboration among staff; 4) establishing a culture of inquiry, innovation and exploration; 5) establishing embedded systems for collecting and exchanging knowledge and learning; 6) learning with and from the external environment and larger learning system; and 7) modelling and growing learning leadership. The dimensions and underlying key characteristics are intended to provide practical guidance on how schools can transform themselves into a learning organisation and ultimately enhance student outcomes
Keywords: Education